Corporate taxation and the welfare state - Christian Keuschnigg (Center for Economic Studies and ifo Institute (CESifo), 2009)
The paper compares the impact of corporate taxation and social insurance on foreign direct investment (FDI) and unemployment. Four main results are derived: (i) the optimal size of the welfare state depends on the degree of risk-aversion and the unemployment rate as a measure of labor income risk. The unemployment rate partly reflects the country's exposure to globalization; (ii) corporate taxation and social insurance have equivalent effects on unemployment and outbound FDI; (iii) while an increase in the corporate tax can raise corporate tax revenue, it is rather likely to worsen the government's total fiscal stance. A corporate tax cut can thus be self-financing due to fiscal increasing returns in the presence of a large public sector; (iv) a corporate tax should be used to contribute to welfare state financing only in exceptional cases when job creation is excessive and unemployment is inefficiently low. These conditions are probably unlikely to hold in Europe's generous welfare states with high structural unemployment rates.
Keywords: F21; H21; H53; J64; J65; 330; Corporate tax; foreign direct investment; unemployment; welfare state; Direktinvestition; Außenhandelseffekt; Sozialstaat; Makroökonomischer Einfluss; Arbeitslosigkeit; Unternehmensbesteuerung; Einkommensteuer; Theorie